2023
DOI: 10.1039/d3cc00138e
|View full text |Cite
|
Sign up to set email alerts
|

One-step topochemical transformation of MoAlB into metastable Mo2AlB2 using a metal chloride salt reaction

Abstract: Reacting MoAlB with ZnCl2 at 550 ºC produces metastable Mo2AlB2 through a one-step topochemical transformation. This reaction showcases differences in reactivity between boride-based MAB phases and carbide-based MAX phases, which...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…We therefore anticipated that the reaction of MoAlB and ZnCl 2 may lead to the formation of a MBene but found that this reaction instead produced Mo 2 AlB 2 ! Specifically, we discovered that Mo 2 AlB 2 can be synthesized in a single step through a bulk-scale reaction between MoAlB and ZnCl 2 at 550 °C, where ZnCl 2 is molten (Figure a,c) . The reaction temperature is sufficiently high to crystallize Mo 2 AlB 2 directly under the conditions of Al deintercalation, which is facilitated by the ZnCl 2 etchant.…”
Section: Targeting Metastable Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…We therefore anticipated that the reaction of MoAlB and ZnCl 2 may lead to the formation of a MBene but found that this reaction instead produced Mo 2 AlB 2 ! Specifically, we discovered that Mo 2 AlB 2 can be synthesized in a single step through a bulk-scale reaction between MoAlB and ZnCl 2 at 550 °C, where ZnCl 2 is molten (Figure a,c) . The reaction temperature is sufficiently high to crystallize Mo 2 AlB 2 directly under the conditions of Al deintercalation, which is facilitated by the ZnCl 2 etchant.…”
Section: Targeting Metastable Compoundsmentioning
confidence: 99%
“…Panel (b) is adapted with permission from ref , copyright 2019 American Chemical Society. Panel (c) is adapted with permission from ref , copyright 2023 The Royal Society of Chemistry.…”
Section: Targeting Metastable Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this does not result in a layered material consisting of separated MXenes, but instead the material shrinks in the direction perpendicular to the MXene planes and collapses into a reconstructed bulk phase. There are also examples of materials with only partial etching of the A layer from MAB phases, closely related to MAX phases, which is clearly not sufficient to comply with successful exfoliation, i.e., for the selective etching to be considered successful in relation to MXene synthesis, the A layer needs to be completely removed while avoiding the etched structure collapsing into a new bulk structure, i.e., the etched MAX phase should consist of chemically inert MXene substructures, not connected by chemical bonding.…”
Section: Computationally Driven Mxene Developmentmentioning
confidence: 99%
“…The resulting Ti 3 C 2 Cl z phase was further reacted with a molten Li 3 N/LiCl/KCl mixture to form N-termination groups. Finally, Baumler et al have also shown that molten-salt etching is feasible with boride compounds like MoAlB, although complete etching was not possible and the process was stopped at the Mo 2 AlB 2 phase.…”
Section: Introductionmentioning
confidence: 99%